Strategy as staged performance: A critical discursive perspective on keynote speeches as a genre of strategic communication. (21st December 2017) - Wenzel, Matthias; Koch, Jochen
Abstract : Research Summary : In this article, we explore how keynote speeches come into being as a staged genre of strategic communication. In our critical discursive analysis of video data on Apple Inc.'s keynote speeches, we demonstrate how keynote speeches are multimodally accomplished through the embodied enactment of four discursive practices: referencing, relating, demarcating, and mystifying. We show how different bodily movements, which we describe as leveling and leaping gestures, systematically contribute to constructing different conceptions of strategy through the enactment of these discursive practices as a staged genre of strategic communication. Our findings contribute to strategy‐as‐practice research by extending the nascent but growing literature on genres of strategic communication, the strategist's body in the strategy process, and the use of video‐based research methods. Managerial Summary : Firms increasingly rely on keynote speeches to communicate their strategies. As a result, managers invest more and more time and effort into preparing and rehearsing their keynote speeches. But how do managers communicate strategy in these staged performances? Based on an analysis of Apple Inc.'s keynote speeches, we explore the discursive and bodily patterns that characterize this genre. In doing so, we demonstrate that the coordinated use of bodily movements in keynote speeches is consequential for highlighting different aspects of the communicated strategy. This shows that keynote speeches and other types of public speeches cannot simply be scripted, but require managers to engage in bodily rehearsal and training in order to communicate strategies effectively. Abstract : Video Abstract